Kombinasi Ekstrak Metanol Daun Ketepeng Cina (Cassia alata Linn.) dengan Enam Ekstrak Tumbuhan Terpilih dalam Menghambat Pertumbuhan Bakteri Staphylococcus aureus - Lisna Hamni; Avidlyandi Avidlyandi; Charles Banon; Khafit Wiradimafan; Deni Agus Triawan; Risky Hadi Wibowo; Morina Adfa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aimed to determine the antibacterial activity and the effect of the combination of methanol extract of the leaves of Chinese ketepeng (Cassia alata Linn.) with six selected plant extracts against Staphylococcus aureus bacteria. The method used is well diffusion and paper tape method. The concentration of the test extract was 100 mg/mL (1:1), DMSO 50% v/v was used as a negative control and the antibiotic clindamycin as a positive control. The results showed that most of the combinations of the methanol extract of the Chinese ketepeng leaf (C. alata) with the six selected plant extracts produced an average diameter of the inhibition zone, which was greater than the average diameter of the inhibition zone of every single extract. However, the average diameter of the combined inhibition zones was not more significant than the sum of the average diameters of the inhibition zones of every single extract. In conclusion, the combination of the methanol extract of the Chinese ketepeng leaf (C. alata) with six selected plant extracts had additive/indifferent effects in inhibiting the growth of S. aureus. Keywords: Antibacterial, Cassia alata Linn, Combination, Staphylococcus aureus